Source Rock Evaluation in the "Idea" Field, Bintuni Basin, West Papua: A Geochemical Approach - Ananda, Dea; Jamaluddin, Jamaluddin; Utomo, Warto; Wiyono, Joko; Ulfah, Baiq Maulinda; Amiruddin, Amiruddin; Manik, Nijusiho; Suprayitno, Abdi (JURNAL GEOCELEBES, 2025)
The Bintuni Basin is one of the largest hydrocarbon-bearing basins in Eastern Indonesia, although only a limited number of oil and gas fields are currently. Consequently, further investigation into its petroleum system, particularly the potential of its source rocks. In hydrocarbon exploration, characterizing source rock is critical to evaluating the presence of organic-rich strata capable of generating hydrocarbons. Geochemical analysis is a widely used method for assessing source rock potential, utilizing total organic carbon (TOC), rock-eval pyrolysis, and vitrinite reflectance data. In this study, geochemical data were obtained from one well and two outcrop samples to evaluate the quantity, quality, and thermal maturity of organic matter. The geochemical assessment of rock samples from four stratigraphic formations indicates that the Permian Ainim Formation exhibits the highest source rock potential. TOC values range from 1% to 80% with hydrogen index (HI) values range between 13 and 431 mg HC/g TOC classifying the formation as a good to excellent potential. The dominant organic matter consists of kerogen type II/III suggesting the potential for both oil and gas generation. Thermal maturity analysis indicates that the Ainim formation has reached the oil and gas generation window at depths of 8,075–8,420 feet. These findings demonstrate that the Ainim Formation represents a significant source rock within the Bintuni Basin, contributing valuable insights into the region's petroleum system and hydrocarbon prospectivity.